Answer:
(5,-1)
Step-by-step explanation:
4x+3y=17
3x+2y=13
So elimination sounds fun but we will have to do manipulation:
Multiply top equation by 2 and bottom equation by 3. This will cause the second term in both by 6y which means we would be setup for elimination.
8x+6y=34
9x+6y=39
--------------------now subtract the equations
-x+0=-5
So x=5
Now plug it into either question (no matter which-pick and choose)
I will go with the second original 3x+2y=13
So if x=5 we have 15+2y=13
Subtract 15 on both sides: 2y=-2
Now divide both sides by 2: y=-1
Answer (5,-1)